PENGENALAN METODE PENELITIAN PENDIDIKAN MELALUI KONSEP DASAR TINDAKAN KELAS - Rahmadani Fitri Ginting; Nurul Hamidah; Muhamad Syahir (Sindoro: Cendikia Pendidikan, 2024)
This article explores the introduction of educational research methods through the basic concept of Classroom Action Research (CAR). Utilizing a qualitative approach, particularly literature review, the study aims to understand and gather data regarding specific phenomena, behaviors, and situations in education. The discussion focuses on the concept of Classroom Action Research (CAR), a method aimed at improving the learning process directly within the classroom environment. CAR involves systematic cycles of planning, action, observation, and reflection, allowing educators to address complex challenges in teaching and learning effectively. The relevance of CAR in enhancing learning quality is significant, empowering educators to develop a research culture, innovate teaching approaches, and collaboratively solve learning problems. While challenges such as limited resources and educational complexities exist, opportunities for further development include comparative studies of CAR methods, technology integration, collaborative research, teacher capacity building, and longitudinal research to understand long-term impacts. Thus, understanding and applying educational research methods, particularly through CAR, proves to be an effective strategy in enhancing learning quality in educational institutions.